2014
DOI: 10.1177/0194599814527730
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Study between the Small Jaw® and the Harmonic Focus® in Open Thyroidectomy

Abstract: Open thyroidectomy for PTC using the HF or the LSJ was safe and effective and was not associated with any increase in complications. Surgical outcomes and operative morbidity were equivalent between the 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…The number of patients admitted following total thyroidectomy or thyroid lobectomy increased by 13 Fig. 1).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The number of patients admitted following total thyroidectomy or thyroid lobectomy increased by 13 Fig. 1).…”
Section: Resultsmentioning
confidence: 98%
“…From 1996 to 2006, hospital charges from inpatient thyroidectomy for thyroid cancer have tripled on an aggregate basis and more than doubled per capita (5,8,13,14). The increasing use of novel surgical instruments, the rising incidence of welldifferentiated thyroid cancer, changing inpatient characteristics, and complication rates have been shown to have a significant financial impact on thyroid surgery (3,(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…2). [12,14] Moreover, funnel plot of operative time in all studies showed no obvious evidence of publication bias (Fig. 3).…”
Section: Resultsmentioning
confidence: 87%
“…[10–16] Among them, 5 studies (386 patients) compared LS Small Jaw and clamp-and-tie, [10,11,13,15,16] and the residual 2 studies (427 patients) compared LS Small Jaw and Harmonic Focus Scalpel for thyroidectomy. [12,14] The baseline characteristics of all studies are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation